Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2006
DOI: 10.1196/annals.1369.063
|View full text |Cite
|
Sign up to set email alerts
|

Morphological Evidence that Xenon Neuroprotects against N‐Methyl‐dl‐Aspartic Acid‐Induced Damage in the Rat Arcuate Nucleus

Abstract: The hyperactivation of glutamate receptors, especially those of the N-methyl-d-aspartate subtype (NMDA), can induce excess calcium entry into cells, leading to neuronal death. Since the anesthetic gas xenon behaves as an NMDA antagonist, the present article investigated, by distinct morphological approaches and after different times, the possible neuroprotectant effects of this gas in a model of neuronal damage induced by N-methyl-dl-aspartic acid (NMA) on rat arcuate nucleus. Rats were assigned to the followi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
22
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 32 publications
2
22
0
1
Order By: Relevance
“…Hemodynamic stability as well as rapid diffusion across the alveolocapillary membrane are only 2 of many unique features provided by xenon. Most notably, xenon is capable of eliciting neuroprotection in conjunction with its anesthetic effects via the inhibition of N-Methyl-D-aspartate (NMDA) receptors, 83,84 as well as protecting the heart and kidney against I/R injury. 85, 86 Organoprotection is mediated via the activation of common prosurvival signaling cascades such as the activation of PI3K/ Akt, PKCε, p38 MAPK, Erk1/2, and mitoK ATP channels.…”
Section: Anesthetic Gases: Nitrous Oxide and Xenonmentioning
confidence: 99%
“…Hemodynamic stability as well as rapid diffusion across the alveolocapillary membrane are only 2 of many unique features provided by xenon. Most notably, xenon is capable of eliciting neuroprotection in conjunction with its anesthetic effects via the inhibition of N-Methyl-D-aspartate (NMDA) receptors, 83,84 as well as protecting the heart and kidney against I/R injury. 85, 86 Organoprotection is mediated via the activation of common prosurvival signaling cascades such as the activation of PI3K/ Akt, PKCε, p38 MAPK, Erk1/2, and mitoK ATP channels.…”
Section: Anesthetic Gases: Nitrous Oxide and Xenonmentioning
confidence: 99%
“…Furthermore, activation of the Akt/protein kinase B pathway is known to be neuroprotective, and hypothermia may protect against ischemic damage by preserving Akt activity, which in turn inhibits some proapoptotic proteins. 45 In addition to NMDA receptor antagonism, 29,30 the mechanisms whereby xenon is neuroproptective may include (1) a general reduction in neurotransmitter release 14 ; (2) inhibition of 2 other subtypes of glutamate receptor channels, ie, the ␣-amino-3-hydroxy-5-methyl-4-isoxazolole propionate and kainate receptors 31 ; (3) reduction in cytosolic proapoptotic Bax protein expression and enhanced Bcl-x L expression (which binds Bax and so is, in effect, antiapoptotic) 18,46,47 ; (4) activation of 2-pore domain K ϩ channels by xenon, which will also enhance neuroprotection 32 ; (5) inhibition of calcium/ calmodulin-dependent protein kinase II, conferring protection against excitotoxicity in vitro 48 ; and (6) increased phosphorylation of transcription factor cAMP-response element binding protein, which may, in turn, upregulate cAMP-response element binding protein-dependent prosurvival genes. 49 -51 Complete NMDA receptor blockade may actually be proapoptotic in the developing brain.…”
Section: Discussionmentioning
confidence: 99%
“…Xenon is an NMDA antagonist. 29,30 Interestingly, the neuroprotective effects appear to exceed those of specific NMDA receptor antagonists, 17 suggesting additional mechanisms of action, such as inhibition of 2 other subtypes of glutamate receptor channels, ie, the ␣-amino-3-hydroxy-5-methyl-4-isoxazolole propionate and kainate receptors, 31 a general reduction in neurotransmitter release, 14 and effects on other ion channels. 32 Having previously demonstrated short-term neuroprotection by xenon in an established HI model, 20,33 we hypothesized that this mixture of "ideal" properties would make the xenon-hypothermia combination a superior post-HI therapy to either treatment alone and would produce better long-term functional outcomes.…”
mentioning
confidence: 99%
“…As a promising progress in the field of neuroprotection, a series of in vitro and in vivo studies in models of hypoxicischemic brain insults have demonstrated the neuroprotective potential and lack of adverse neurotoxic effects of the chemically and metabolically inert noble gases xenon, argon, and helium (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31). Uniquely among these above-mentioned gases, xenon has been shown to be a NMDA receptor antagonist (32)(33)(34) and a tPA inhibitor (35), allowing to obtain both neuroprotection and inhibition of tPA-induced proteolysis if given after, but not during, ischemia and tPA-induced thrombolysis (35).…”
mentioning
confidence: 99%